Data Loam. Sometimes Hard, Usually Soft. The Future of Knowledge Systems - Paganelli, Mattia (Edition Angewandte, 2021)
As an urgent response to the continually growing flood of information to which libraries, search engines, and cultural institutions are exposed, Data Loam combines radical approaches and strategies from the international practice of contemporary art in essays on artificial intelligence, cybernetics, and cryptoeconomics that put forward sensual logic, causal permeability, and new forms of man-machine interaction.